Concanavalin A-induced Aggregation of Human Blood Platelets - Patscheke, Heinrich; Brossmer, Reinhard (Thrombosis and Haemostasis, 1975)
Concanavalin A (CON A) causes platelets to aggregate. A Ca++-independent effect of CON A could be separated from a main effect which depends on Ca++. The main effect probably is a consequence of the CON A-induced platelet release reaction and therefore is platelet-specific. The weak residual effect observed in the presence of Na2EDTA may be due to a similar mechanism as has been demonstrated for CON A-induced aggregations of several other normal and malignant transformed animal cells.Na2EDTA did not inhibit the carbohydrate-specific binding capacity of CON A. Therefore, Na2EDTA appears not to demineralize the CON A molecules under these experimental conditions.α-methyl-D-glucoside inhibits the Ca++-independent as well as the Ca++-dependent effect of CON A.Pretreatment by neuraminidase stimulated the platelet aggregation induced by CON A. It is possible that removal of terminal sialic acid residues makes additional receptors accessible for the binding of CON A.